258. Preliminary survey on incidents and near-missed in Magnetic Resonance Imaging. (December 2018) - Strocchi, S.; Oberhofer, N.; Matheoud, R.; Mangili, P.; Busoni, S.
Abstract : Purpose: This work presents the preliminary results of a survey made amongst medical physicists on a voluntary basis about the incidents and near-misses they observed in their MRI sites. The purpose is to share as much as possible personal experience, in order to identify the most common risk factors. Methods: This preliminary survey merges the results of two information sources: (1) collection of adverse events and near miss reports carried out among 120 participants of an MRI safety course held in Bolzano in 2013, (2) recent survey amongst medical physicists member of the AIFM working group on Advanced QC in MR, through two specifically conceived models. One model was on minor adverse events concerning patient abnormal heating. The other was on near missed adverse events concerning MRI unsafe or conditional objects. The data were collected anonymously. Results: The total reported events were 28. The most common involved projectile objects. On a total of 23 of those events, 2 involved oxygen cylinders, 5 floor polishers, 16 other objects. The persons directly responsible of the reported events were: 7 cleaner people, 5 from anaesthesia units, 7 RM personnel, 2 specialised external personnel, 4 generic external personnel, 3 others (see Fig. 1). The reporters estimation, when present, indicated the following as potential remedies: training (16 cases), metal detector use (2 cases), other (5 cases). Conclusions: The implementation of a database of adverse events in MR, to be shared amongst physicists responsible for safety and related staff training, could represent a valuable tool for implementing risk reduction actions efficiently.